Determinants of Physical Activity in Arthritic Adults: Insights from Low Socio-economic Settings in India - Amit Kumar Mallik; Sanyal Kumar; Harsh Vardhan; Anjani Kumar; Sanjay Kumar Pandey (Indian Journal of Physical Medicine & Rehabilitation)
Background/Objective: Arthritis, encompassing both osteoarthritis (OA) and rheumatoid arthritis (RA), represents a significant contributor to disability worldwide, affecting a substantial number of adults. Engaging in regular exercise and physical activity is fundamental to managing these conditions; however, a large proportion of arthritis patients remain physically inactive. Understanding the factors influencing activity levels is crucial for developing tailored interventions. This study aimed to investigate and contrast the key determinants influencing physical activity and exercise behaviours in individuals diagnosed with OA and RA. Materials and Methods: A cross-sectional observational study was performed over 12 months at a tertiary care facility, involving 88 participants (44 OA and 44 RA) between the ages of 30 and 60 years. Survey-based interviews were used for data collection with the physical activity and disability survey and assessments of explanatory variables such as self-efficacy, outcome expectations, pain, disability, body mass index and social support. Results: Results indicated that self-efficacy consistently emerged as a primary predictor of physical activity across both groups. Other factors, such as pain and functional limitations, exhibited variations between OA and RA populations. Conclusion: This study underscores the critical role of self-efficacy in fostering physical activity among individuals with arthritis. The findings highlight the necessity of personalised interventions aimed at enhancing self-efficacy and addressing specific barriers faced by OA and RA patients to promote better physical activity outcomes.